HAIC as a potential therapy for esophageal cancer patients with liver metastasis: a retrospective cohort study - Dong, Fengxiao; Cao, Guang; Lu, Zhihao (Frontiers in Medicine, 2023)
Abstract: The role of hepatic arterial infusion chemotherapy (HAIC) in esophageal squamous cell cancer (ESCC) patients with liver metastasis (LM) has not been reported commonly. This study aimed to explore the benefits and tolerability of HAIC in ESCC patients with LM. Methods: This was a single-arm historical cohort study of ESCC patients with synchronous or heterochronous LM between 12/2014 and 07/2021 at the department of Gastrointestinal Oncology. The patients were treated with HAIC for LM, and regular image assessments were done according to the judgment of the interventional physician. Liver progression-free survival (PFS), liver objective response rate (ORR), liver disease control rate (DCR), overall survival (OS), adverse events (AEs) ,treatment information and the basic characteristic were observed retrospectively. Results: Overall, a total of 33 patients were enrolled in this study. All included patients received catheterized HAIC therapy, with a median of 3 (range 2, 6) sessions. The treatment response of liver metastatic lesions included PR in 16 (48.5%) patients, SD in 15 (45.5%) patients, and PD in 2 (6.1%) patients, for an ORR of 48.5% and a disease control rate (DCR) of 93.9%. The median liver PFS was 4.8 months (95% CI 3.0-6.6 months), and the median OS was 6.4 months (95% CI 6.1-6.6months).Patients who achieved PR in liver metastasis site after HAIC were more likely to have a longer OS than those achieved SD or PD. Grade-3 adverse events occurred in 12 patients. The most common grade-3 AE was nausea, in 10 (30.0%) patients, followed by abdominal pain in 3 (9.1%) patients. Only one patient showed grade-3 elevation of alanine aminotransferase(ALT)/aspartate aminotransferase(AST), and one patient suffered from grade-3 embolism syndrome. A grade-4 adverse event, abdominal pain, occurred in one patient. Conclusion: HAIC might be an option as a regional therapy for ESCC patients with LM, as it is acceptable and tolerable.